The Second Vatican Council on other religions - O'Collins, S J Gerald (Oxford University Press, 2013)
Gerald O'Collins explores the full scope of the positive teaching by the Second Vatican Council (1962-65) on other living faiths, illustrating how the Council made a startling advance in official Catholic teaching and how this teaching was borne out in the work of Pope John Paul II and Jacques Dupuis.